1991
DOI: 10.1182/blood.v77.12.2688.bloodjournal77122688
|View full text |Cite
|
Sign up to set email alerts
|

'Role of bone marrow stromal cells in the growth of human multiple myeloma

Abstract: We have verified the hypothesis that multiple myeloma (MM) may be disseminated by circulating clonogenic cells that selectively home to the bone marrow (BM) to receive the signal(s) leading to proliferation, terminal differentiation, and production of the osteoclast activating factors. Long-term cultures of stromal cells have been developed from the BM of nine patients with MM. These cells were mostly fibroblast- like elements, interspersed with a proportion of scattered macrophages and rare osteoclasts. BM st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 31 publications
1
47
0
2
Order By: Relevance
“…Gartner and Kaplan (34) showed that the adherent cell layers in murine LTBMCs consist of mononuclear phagocytic cells, endothelial cells and adipocytes. Caligaris-Cappio et al (39) used slightly different culture conditions for human LTBMCs and described the adherent cell layers as fibroblast-like cells interspersed with macrophages and rare osteoclasts. A previous study of skin and fetal lung fibroblasts showed no expression of YKL-40 in these cells in vitro (25) suggesting that the YKL-40 expression seen in the adherent cell layers from LTBMCs are more likely caused by macrophages or osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Gartner and Kaplan (34) showed that the adherent cell layers in murine LTBMCs consist of mononuclear phagocytic cells, endothelial cells and adipocytes. Caligaris-Cappio et al (39) used slightly different culture conditions for human LTBMCs and described the adherent cell layers as fibroblast-like cells interspersed with macrophages and rare osteoclasts. A previous study of skin and fetal lung fibroblasts showed no expression of YKL-40 in these cells in vitro (25) suggesting that the YKL-40 expression seen in the adherent cell layers from LTBMCs are more likely caused by macrophages or osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…The first data about an expanded pool of OCPs in specific pathologies were published on Paget disease (10). In multiple myeloma, PBMCs from patients with bone lesions gave rise to OCs that resorbed bone in vitro, when cultured in presence of human stromal cells derived from bone marrow (33). The discovery of a pivotal role of RANK, RANKL, and OPG in regulating osteoclastogenesis was substantial for the comprehension of the mechanisms of bone resorption (11-13, 15, 34).…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiological mechanisms of osteolysis focus on the predominant role of osteoclasts in the formation of myeloma osteolytic lesions (Caligaris-Cappio et al, 1991). The growth of myeloma cells in the experimental severe combined immunodeficiency (SCID) human system, as well as in MM patients, is associated with the increased differentiation of osteoclasts (Yacobby et al, 1998) as a result of their interaction with stromal cells (Chauhan et al, 1996).…”
Section: Discussionmentioning
confidence: 99%